O papel do capital social e do alinhamento estrat??gico no isomorfismo de uma rede intraorganizacional: a pedagogia do exemplo em uma organiza????o esportiva - Oliveira, Talmo Curto de (2016)
Sport is a phenomenon that is growing worldwide. It is used by various social actors in different ways and goals. This study aims to verify the existence of social capital and intra-organizational strategic alignment are mechanisms that influence the isomorphism of Example pedagogy among practitioners student-athletes Program Athlete of the Future SESI / SP. The theoretical framework was based on the fundamental concepts of social capital, strategic alignment, and isomorphism intraorganizational networks, rescuing the history of the sport phenomenon. For this purpose, it is planned research into two phases. At first, there was a collection of primary data through semi-structured interview with a director and a sports specialist SESI/SP, along with documentary secondary data. Basis of these results, a quantitative research tool, a questionnaire was developed and applied to student-athletes SESI/SP in order to understand what their perceptions of the initiatives of the SESI/SP managers. It was noticed that the isomorphic behavior, critical to the implementation of programs that seek to spread and repeat morally accepted behavior, has a greater chance of acceptance and absorption in student-athletes sports organizations when there is social capital. In particular, when there is the feeling of belonging, community and sense of community. They are therefore social networking elements and non-structural mechanisms of strategic alignment that allow this type of program in sports organizations. Visa point of substantive domain, it has to be the sports organizations managers who want to implement this type of program or strengthen what already exists should invest in better relationships between individuals, especially in teacher relations and student-athletes to that this type of program has greater chances of success.